THE RELATIONSHIP AMONG MARKETING MIX, SATISFACTION, AND REPURCHASE INTENTION ON SMARTFREN USERS AT BRAWIJAYA UNIVERSITY - Akbar H, Rakhmansyah Wildan; Zain, Djumilah (Jurnal Ilmiah Mahasiswa FEB, 2014)
Repurchase intention by consumers is one of the most important things that must be maintained by the marketer. The reason is the diminishing market share due to the increase in the number of competitors. Marketers have utilized a variety of ways to increase the repurchase by the consumer, including maximizing the marketing mix to gain customer satisfaction, because customer satisfaction is the key to repurchase intention. This study aims to determine the effect of marketing mix to repurchase intention through satisfaction. The analysis used in the study is path analysis with 100 Smartfren users as samples. The sampling technique was purposive sampling. Validity test and reliability test is conducted for instrument testing. The study results indicate that the marketing mix variables only have significant positive effect on repurchase intention when through satisfaction. Satisfaction is variable with the most influence on repurchase intention. Smartfren need to develop a marketing mix to maintain customer satisfaction and repurchase from customers. Keywords: Smartfren, Marketing Mix, Satisfaction, Repurchase Intention Â